Dimethyl fumarate: a possible exit strategy from natalizumab treatment in patients with multiple sclerosis at risk for severe adverse events. Issue 12 (26th August 2017) - Calabrese, Massimiliano; Pitteri, Marco; Farina, Gabriele; Bajrami, Albulena; Castellaro, Marco; Magliozzi, Roberta; Monaco, Salvatore
Abstract : Introduction: Among disease-modifying treatments for multiple sclerosis, natalizumab (NTZ) is highly effective, well tolerated and generally safe. Major concerns regard the risk of developing progressive multifocal leukoencephalopathy (PML), and the occurrence of rebounds or disease activity after its discontinuation. The aim of this study was to explore the efficacy of dimethyl fumarate (DMF) in preventing disease reactivation after NTZ discontinuation. Methods: Thirty-nine patients with relapsing remitting multiple sclerosis, at high risk of PML, were switched from NTZ to DMF and underwent neurological and 3T MRI monitoring for 2 years. Clinical and MRI data regarding the 2-year period preceding NTZ treatment, the 2 years of NTZ treatment and the 2 years of DMF were collected. Results: During the DMF phase, among the 39 patients, one or more relapses occurred in five patients (12.8%), increased disability progression in 4 (10.3%) and MRI activity in 8 (20.5%). Post-NTZ rebound effect was observed only in one patient. Overall, only two dropouts (one rebound activity and one gastrointestinal side effect) were registered and almost 80% of the patients have still no evidence of disease activity at the end of DMF treatment. The multiple linear regression model revealed that the number of relapses and MRI parameters before DMF treatment were good predictors of disease activity during treatment with DMF. Discussion: DMF appeared generally safe and no carryover PML among investigated cases was observed. Although DMF did not eliminate the possibility of disease reactivation, it seems anyway a promising drug for those patients who shall discontinue NTZ. The clinical and radiological activity preceding the DMF treatment might be used as a prognostic marker of therapy response.